105 A CASE OF RARE ATYPICAL ATRIAL STRUCTURE. (15th December 2022) - Lalario, Andrea; Maione, Davide; Carriere, Cosimo; Merlo, Marco; De Luca, Antonio; Sinagra, Gianfranco
Abstract: A 27-year-old woman, without previous cardiological history, was admitted at our emergency department in the clinical context of an acute pericarditis. Echocardiography documented mild pericardial effusion (8 mm) without any sign of hemodynamic impact. The patient was then admitted at our Cardiology Unit. During the hospitalization a complete transthoracic echocardiogram showed a normal biventricular morphology and function, normal valvular function and found an anechoic structure on the postero-lateral left atrial wall (1.75×1.5 cm). To better characterize this accidental finding, a transesophageal echocardiography was performed unmasking a dilated coronary sinus with anomalous course. A subsequent cardiac computed tomography was performed showing anomalous systemic venous return with the persistency of the left superior vena cava draining into the coronary sinus. No other congenital anomalies were found. PLSVC is present in approximatively 0.5% of individuals in the general population and is the most frequent congenital malformation of the thoracic venous return. In about 90% coexists with the right superior vena cava and co-occur in almost 40% of patients with other congenital heart abnormalities such as atrial septal defect, aortic coarctation, bicuspid aortic valve, tetralogy of Fallot, transposition of the great vessels, anomalous connections of the pulmonary veins, dextroversion and cor triatatum. Patients usually are asymptomatic. Nevertheless, this congenital malformation may cause chest discomfort, cardiac arrhythmias, thromboembolic events, decreased exercise tolerance and syncope. Moreover, the correct identification of this condition has important clinical implications. In fact, it is a relative contraindication to the administration of retrograde cardioplegia during cardiac surgery. Furthermore, the placement of central venous-access line, pulmonary artery catheterization or the implantation of pacemaker/resynchronization leads could be difficult or can result in incorrect positioning. In these cases, it is recommended to access to the right heart through the right subclavian vein instead the left one. Legend: *: Anomalous course of coronary sinus; LA: Left Atrium; LV: Left Ventricle; Ao: Aorta; RA: Right Atrium; R-SVC: Right superior vena cava; L-SVC: Left superior vena cava; LSPV: Left superior pulmonary vein.